2022
DOI: 10.1111/1467-968x.12233
|View full text |Cite
|
Sign up to set email alerts
|

Loan Word Accommodation Biases: Markedness and Finiteness

Abstract: One way or another, loan words have to be grammatically integrated in the grammar of their recipient language. For verbs, Wohlgemuth (2009) finds that direct insertion, where native inflections are added directly onto the borrowed stem, is cross‐linguistically the most frequent accommodation strategy. He concludes from this that the borrowing of loan verbs is not constrained by inflection. Based on a two‐fold corpus study on the integration of English loan verbs in Present‐day Dutch and French loan verbs in La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…More specifically, De Smet and Shaw (forthcoming) argue that French-origin verbs are subject to what they call "accommodation biases," that is, morphosyntactic constraints: in their study of the fifteen most frequent verbs of French origin during the Middle English period, the share of finite forms is lower than expected in nearly every case. Furthermore, Shaw and De Smet (2022) have also shown in another study that, compared to native verbs, the use of auxiliary do is favored with French-origin verbs over the finite alternative in the period 1500-1570 (Shaw & De Smet 2022). In addition to these studies, it is also worth stressing that the practice of inserting a semantically light verb to help the adoption of foreign words is not uncommon crosslinguistically.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…More specifically, De Smet and Shaw (forthcoming) argue that French-origin verbs are subject to what they call "accommodation biases," that is, morphosyntactic constraints: in their study of the fifteen most frequent verbs of French origin during the Middle English period, the share of finite forms is lower than expected in nearly every case. Furthermore, Shaw and De Smet (2022) have also shown in another study that, compared to native verbs, the use of auxiliary do is favored with French-origin verbs over the finite alternative in the period 1500-1570 (Shaw & De Smet 2022). In addition to these studies, it is also worth stressing that the practice of inserting a semantically light verb to help the adoption of foreign words is not uncommon crosslinguistically.…”
Section: Discussionmentioning
confidence: 88%
“…The idea that the large influx of French items played a role in the use of auxiliary do has been suggested by various scholars. Fischer and van der Wurff (2006:155) mention it as a possible factor that may have helped the rise of auxiliary do , while Shaw and De Smet (2022) have shown that French-origin infinitives favor the use of auxiliary do in Early Modern English, particularly in the period 1500-1570 (see section 5 for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Several models have been proposed to approach the topic of loan verb integration, but the theory of verbal borrowing typology introduced by Wohlgemuth ( 2009) is widely recognized as the most effective and well-known one. It has served as the theoretical framework for numerous studies on loan verb accommodation in various languages worldwide, including those conducted by Amirideze (2018), Bhattacharja (2010), Forker (2021, Hassan (2018), Ralli (2016), Shaw andDe Smet (2022), andVučković (2017), among others. In the current study, Wohlgemuth's theory of verbal borrowing typology is also utilized, with a particular focus on the different strategies of loan verb integration.…”
Section: Models Of Loan Verb Integrationmentioning
confidence: 99%
“…In this context, several studies have investigated the different strategies used to integrate borrowed verbs in various languages worldwide, such as Coptic (Grossman, 2019), Dutch and French (Shaw and De Smet 2022), Georgian (Amiridze 2018), Hungarian (Nemeth 2015), Kurmanji Kurdish (Çabuk 2019),…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation